Cultural Competence In Nursing Care For Saudi Patients (The Review of Diabetic Studies, 2024)
Introduction: The Kingdom of Saudi Arabia (KSA) is a unique country in terms of the high percentage of expatriate professionals involved in the provision of care to its population whose values are deeply rooted in Islamic and traditional beliefs. With the development of the healthcare sector within the framework of Saudi Vision 2030, the attainment of cultural competence, or the capability to deliver care in line with the cultural and religious convictions and beliefs of a patient, has become a national imperative to maintain patient safety and quality care.Objective: The systematic review aims to examine the cultural competence of nurses providing healthcare to Saudi Arabian patients and the factors associated with providing culturally appropriate nursing care to Saudi citizens.Method: A search was carried out systematically in several databases, such as PubMed, CINAHL, and the Saudi Medical Journal, to find the peer-reviewed articles published in 2015-2026. Based on PRISMA recommendations, a narrative synthesis of 11 selected studies with either quantitative, qualitative, and mixed-method designs was conducted. Data were analyzed and coded on the themes of linguistic difficulties, religious sensitivities, and organizational support.Conclusion: The review reveals that there is a large gap in terms of preparedness in which nurses are highly culturally aware but lack practical competence in altering care that Saudi patients receive. Barriers are greatest in terms of language barriers and gender-concordance. In order to fulfill the requirements of the Vision 2030, healthcare facilities will have to go beyond the simple orientation to standardized, longitudinal cultural training and simple medical Arabic instruction to expatriate personnel in order to close the gap between the technical care and cultural respect.